Les familles immigrées aux marges de l’école. Dépendance et mobilisation des parents dans le contexte d’un quartier populaire - Pierre Périer (Cahiers de la Recherche sur l'Education et les Savoirs)
Policies of cooperation between schools and families trigger role expectations towards parents who have unequal resources to meet them. This is the case of the immigrant families investigated in a disadvantaged neighborhood through qualitative interviews: most of them are confronted with similar difficulties than working-class families but also present differences related to their migration background and trajectories. While these families have high aspirations for their children, they do not have the competences required in order to tackle efficiently schooling issues, including the relationship to build with the school staff. It is argued in this article that these parents are at odds with the school institution, and even marginalized, as if their actual support for their children’s education and their involvement remain invisible, at the risk of their social exclusion and stigmatization.